Cantharidin suppressed breast cancer MDA-MB-231 cell growth and migration by inhibiting MAPK signaling pathway - Gu,X.-D. (2017)
As an active constituent of the beetle Mylabris used in traditional Chinese medicine, cantharidin is a potent and selective inhibitor of protein phosphatase 2A (PP2A) that plays a crucial role in cell cycle progression, apoptosis, and cell fate. The role and possible mechanisms exerted by cantharidin in cell growth and metastasis of breast cancer were investigated in this study. Cantharidin was found to inhibit cell viability and clonogenic potential in a time- and dose-dependent manner. Cell cycle analysis revealed that cell percentage in G2/M phase decreased, whereas cells in S and G1 phases progressively accumulated with the increasing doses of cantharidin treatment. In a xenograft model of breast cancer, cantharidin inhibited tumor growth in a dose-dependent manner. Moreover, high doses of cantharidin treatment inhibited cell migration in wound and healing assay and downregulated protein levels of major matrix metalloproteinases (MMP)-2 and MMP-9. MDA-MB-231 cell migration and invasion were dose-dependently inhibited by cantharidin treatment. Interestingly, the members of the mitogen-activated protein kinase (MAPK) signaling family were less phosphorylated as the cantharidin dose increased. Cantharidin was hypothesized to exert its anticancer effect through the MAPK signaling pathway. The data of this study also highlighted the possibility of using PP2A as a therapeutic target for breast cancer treatment.